Biogeotechnical approach for slope soil stabilization using locally isolated bacteria and inexpensive low-grade chemicals: A feasibility study on Hokkaido expressway soil, Japan. - Gowthaman, S. (Elsevier., 2019)
Microbial Induced Calcite Precipitation (MICP) is one of the most popular biotechnological soil stabilization techniques since it results in significant improvements in the geotechnical properties of soil. The current study presents a laboratory-scale MICP investigation performed to demonstrate the feasibility of slope soil stabilization of the Hokkaido expressway through surficial treatment. The objectives of this preliminary study are to investigate the feasibility of (i) augmenting indigenous bacteria, and (ii) implementing commercially available inexpensive low-grade chemicals in microbial induced solidifications. Syringe solidification tests were carried out using indigenous ureolytic bacteria under various temperature condition with the use of different injection sources. A high strength crust layer was achieved on the soil surface with 420 kPa unconfined compressive strength (UCS) as measured by needle penetration test after 10 days of treatment using pure chemicals (30 C; 0.5 M cementation solution, every 24 h; bacterial culture solution, only at the beginning). However, by substituting pure chemicals with low-grade chemicals, a significant improvement in the UCS of soil (820 kPa at 30 C) was obtained together with a 96% reduction in the treatment cost. The morphologies and crystalline structures of the precipitated carbonate were characterized by Scanning Electron Microscopical (SEM) observations. This alternative approach of introducing low-grade chemicals in MICP has the potential to provide significant economic benefits in field-scale applications.
Keywords: Microbial induced calcite precipitation.; Indigenous bacteria.; Pure chemicals.; Low-grade chemicals.; Slope soil stabilization.